The experiences of caregivers of Indigenous cancer survivors in Australia, Canada, New Zealand and the United States: a systematic review. - Masa, A.J.; Martinez-Bredeck, H.; Butler, T.L.; Anderson, K.; Girgis, A.; Aoun, S.; Cunningham, J.; Wakefield, C.E.; Shahid, Shaouli; Smith, A.B.; Garvey, G. (2022)
Background: Caregivers of Indigenous cancer survivors provide critical unpaid support to survivors, yet they rarely receive information or training for this role and may themselves benefit from support services. Little is documented about the experiences of caregivers of Indigenous cancer survivors. The aim of this systematic review was to identify and aggregate qualitative research describing the experiences of caregivers of Indigenous cancer survivors in Australia, New Zealand, Canada and the United States.